Purchasing Power Parity: Further Evidence from African Countries (2011)
In this paper we pursue an empirical enquiry into the validity of an equilibrium absolute purchasing power parity (PPP) for a sample of 26 economies in Africa. Using univariate as well as panel unit root tests on yearly observations spanning 1973 to 2008, we uncover evidence that the PPP notion holds in just a little over one third of the countries selected and breaks down on average when the latter class of tests are employed. In sum, non-linear modelling of exchange rate convergence to its PPP trajectory could foster understanding on the subject.